Room Temperature Field Characteristics with Multi- air-conditioner in Operation - 吴丹尼; 陈伟; 萧峰 (Zhileng xuebao)
The experiments were conducted to determine the influences of some factors on the air flow fields and temperature distributions in an air-conditioned room.The results show that the positioning of the air-conditioners influences the cooling rate dominantly and the air discharging angle and speed also have certain effect.In particular,the average indoor temperature decreases faster when the two air conditioners are at opposite ends of the room long side and the air discharges in the horizontal direction.Moreover,the air temperature drops more slowly when the two air conditioners stand corner to corner in the cross.In addition,the temperature field has the minimum temperature difference when cool air issues at an angle of 120 degrees.